2021
DOI: 10.1016/j.xphs.2020.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Aggregated Antibody-Silicone Oil Complexes: From Perspectives of Morphology, 3D Image, and Fcγ Receptor Activation

Abstract: Pre-filled syringes (PFS) have been in widespread use as an administration device for therapeutic antibodies in recent decades. Generally, the inner barrel and syringe of PFS are coated with silicone oil (SO) for lubrication. Multiple studies have focused on the fact that the SO adsorbs denatured antibody molecules, and induces antibody aggregation. Aggregated antibodies are recognized as a potential risk for evoking immunogenic responses in patients. The characteristics of the aggregated antibody-SO complexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…8 Thus, it is especially important to control the quality of protein drugs during transportation. In fact, it has been reported that antibodies might aggregate by dropping or vibrating, 9 and the complexes of SO droplets with antibodies might cause immune responses, 10,11 suggesting that changes in the physical properties of proteins can lead to changes in biological responses. Furthermore, it has been implied that higher concentrations of subvisible particles in the vials of peginesatide (PEGylated peptides binding to the erythropoietin receptor) might be related to the occurrence of anaphylaxis upon its administration.…”
Section: 6mentioning
confidence: 99%
“…8 Thus, it is especially important to control the quality of protein drugs during transportation. In fact, it has been reported that antibodies might aggregate by dropping or vibrating, 9 and the complexes of SO droplets with antibodies might cause immune responses, 10,11 suggesting that changes in the physical properties of proteins can lead to changes in biological responses. Furthermore, it has been implied that higher concentrations of subvisible particles in the vials of peginesatide (PEGylated peptides binding to the erythropoietin receptor) might be related to the occurrence of anaphylaxis upon its administration.…”
Section: 6mentioning
confidence: 99%
“…We attempted to build a classification model by applying two machine learning methods, decision tree [27] and random forest [28], to MFI and FlowCam data (Supplemental Table 5-1). R was used for model building, and J4.8 was used for the decision tree algorithm, implemented with "RWEKA", an R package WEKA [28]. For the random forest, we used the "randomForest" package.…”
Section: Machine Learningmentioning
confidence: 99%
“…Discussion was divided on whether accuracy should be prioritized for SO droplets or protein particles. While protein aggregates are generally believed to be related to the immunogenicity of biopharmaceuticals, it was also reported that soluble and/or insoluble proteins accumulation around SO droplets may elicit undesired immune responses [14,28,29]. Continuously monitoring lot-to-lot consistency in protein particles and SO droplets would be crucial to ensure the quality and safety of prefilled syringe products.…”
Section: Building Streamlined Decision Treesmentioning
confidence: 99%
“…Silicone oil acting as a lubricant is precoated in the PFS glass barrel to maintain its functionality. It has been reported in various studies that silicone oil is prone to migrate from the glass barrel into formulation along staging. Importantly, previous studies have shown that silicone oil and protein molecules can interact to form protein–silicone oil particle mixtures. Although silicone oil by itself is often considered innocuous, silicone oil–protein particle mixtures may have immunogenic properties . In light of potential immunogenic concerns, efforts have been made to eliminate silicone oil in syringes to improve formulation stability through the development of silicone oil-free syringes. , Current methods to study and quantify drug solution particles include light obscuration (HIAC), microflow imaging (MFI), and imaging flow cytometry (IFC). These industry gold standards mostly acquire morphological features such as Feret diameter, aspect ratio, circularity, and intensity .…”
Section: Introductionmentioning
confidence: 99%